Financing solar photovoltaic transitions: From utility to residential market adoption in emerging economies - Ranaporn Tantiwechwuttikul; Masaru Yarime (Asian Development Bank Institute (ADBI), 2018)
Solar photovoltaic (PV) technological leap-frogging greatly enhances energy accessibility, yet energy affordability remains a critical challenge. Traditional financing options, categorized as the solar-as-asset model, usually favor utility-scale PV projects, whereas the investment growth in smaller-scale PV systems is far behind, particularly in emerging countries. To further untapped PV potentials, we need to promote technological adoption in non-utility markets. That requires alternative financing approaches, such as the solar-as-service model. This paper examines the advantages and disadvantages of different financial schemes for introducing PV facilities in terms of the suitability of funding vehicles and investment mechanisms. Given the policy expense curtailment, owing to the gradual PV competitiveness, our analysis particularly focuses on the emerging market for PV installations for self-consumption. As the main obstacle is the high upfront cost of PV systems, we examine the new financial models in which customers buy the service rather than PV system per se. We consider what conditions would be necessary to facilitate the third-party ownership models and alternative financing schemes. Finally, this paper discusses what policy measures and instruments can be deployed to foster further PV adoption in the context of emerging economies. This study also provides implications for corporate strategy and financial institutions.
Keywords: O16; O33; Q48; 330; PV investment models; PV price competitiveness; distributed PV system; solar-as-service; solar third-party ownership